Perbandingan Praktik Manajemen Kredit dalam Mencegah Kredit Macet pada Koperasi Murah Hati dan Koperasi Patuh Karya di Kabupaten Lombok Timur - Nadila Afriliana; Muhammad Zainul Majdi; Pahrudin Pahrudin (Jurnal Riset Akuntansi, 2026)
This study is motivated by the importance of effective credit management in ensuring the sustainability of savings and loan cooperatives, particularly in reducing non-performing loans. Differences in credit management practices across cooperatives represent a relevant issue, especially in balancing formal system-based approaches and trust-based social mechanisms. This study aims to analyze and compare credit management practices in preventing loan defaults at Koperasi Murah Hati and Koperasi Patuh Karya in East Lombok Regency. A qualitative approach with a comparative design was employed. Data were collected through in-depth interviews, observation, and documentation involving cooperative management and borrowing members, and analyzed using data reduction, comparative tabulation, and descriptive-analytical interpretation. The findings reveal that Koperasi Murah Hati applies a trust-based approach characterized by simplified procedures without collateral and field verification, while Koperasi Patuh Karya implements a more formal system through administrative verification, feasibility assessment, and collateral requirements. However, Koperasi Murah Hati shows a lower non-performing loan rate (3.7%) compared to Koperasi Patuh Karya (10.5%). These findings indicate that effective credit management is influenced not only by formal systems but also by social factors such as trust and communication.